Executive Summary - Princes, Elfindah (APPS Publications, 2024)
As the Chief Editor of the Journal of Multidisciplinary Issues, I am honored to present this special edition that explores the profound impacts of emerging technologies, particularly artificial intelligence (AI), on various aspects of society, education, and consumer behavior. This issue features a diverse collection of research papers that provide critical insights into the challenges and opportunities presented by AI and digital platforms. In